Analysis of Students' Difficulties in Solving Mathematics Problems Based on High Order Thinking Skill (HOTS) Based on Polya Heuristic Stages at SMP Negeri 15 Medan - Yusni Utami; Ade Andriani (Formosa Journal of Multidisciplinary Research, 2023)
In solving math problems, especially HOTS-based math problems, students often have difficulty solving them. One effort that can be done to overcome students' difficulties in solving HOTS-based math problems is by describing the difficulties and factors that result in students having difficulty completing HOTS-based math problems based on Polya heuristic stages. The stages of Polya's heuristics in solving problems are: (1) Understanding the problem; (2) Devising A Plan; (3) Carrying Out The Plan (implementing the plan) and (4) Looking Back (looking back at the completion). The purpose of this study is to describe students' difficulties, the difficulties experienced by students in solving HOTS-based math problems and to describe student answers based on the Polya Heuristic Stages. The subjects in this study were class VIII-4 students of SMP Negeri 15 Medan, totaling 31 students. The approach used in this research is a descriptive qualitative approach.